Patients' experiences of cognitive functioning in recurrent depression: A qualitative study. Issue 4 (5th February 2020) - Crowe, Marie; Porter, Richard; Douglas, Katie; Inder, Maree; Lacey, Cameron; Jordan, Jennifer; Wells, Hayley
Accessible summary: What is known on the subject?: Recurrent depressive episodes involve significant morbidity, suicide risk and recurrent hospitalizations. In both major depressive disorder and bipolar disorder, there are significant impairments in functioning following resolution of acute symptoms. What this paper adds to existing knowledge?: This paper provides an in‐depth qualitative understanding of the subjective experience of cognitive impairment following a depressive episode in a recurrent mood disorder. It identifies descriptions of two types of experience (being stuck and being preoccupied with one's thoughts) that led to impairments in concentration, memory, organization and decision‐making. What are the implications for practice?: Mental health nurses need to develop an awareness of the impact of cognitive difficulties in the process of recovery from recurrent mood disorders. Mental health nurses need to provide knowledgeable reassurance, information and interventions to people who experience cognitive difficulties to provide a framework of understanding that promotes recovery. Abstract: Introduction: People who experience recurrent depressive episodes often have ongoing cognitive problems that impact on their functional recovery. These cognitive difficulties have been identified as impacting on social, interpersonal and occupational functioning and can result in vulnerability to relapse. Aim: The aim of this qualitative study was to explore participants' subjective experiences of cognitive impairment after discharge from mental health services following treatment for recurrent depression. Methods: The study was designed as a qualitative study in order to best capture participants' subjective experiences. Data were collected by semi‐structured interviews and were analysed using a process of thematic analysis. Results: Twenty participants took part in this study. All participants described experiences of either 1) "being stuck"; or 2) "being preoccupied with own thoughts"; however, all participants described the experiences in the third theme: "it stops you living to your potential." Implications for practice: In order to promote recovery in a meaningful way, mental health nurses need to provide information about and strategies for managing cognitive difficulties associated with recurrent mood disorders.